2012
DOI: 10.1371/journal.pntd.0001564
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protective Efficacy of a Chimeric Form of the Schistosomiasis Vaccine Antigen Sm-TSP-2

Abstract: The large extracellular loop of the Schistosoma mansoni tetraspanin, Sm-TSP-2, when fused to a thioredoxin partner and formulated with Freund's adjuvants, has been shown to be an efficacious vaccine against murine schistosomiasis. Moreover, Sm-TSP-2 is uniquely recognised by IgG1 and IgG3 from putatively resistant individuals resident in S. mansoni endemic areas in Brazil. In the present study, we expressed Sm-TSP-2 at high yield and in soluble form in E. coli without the need for a solubility enhancing fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 32 publications
3
67
0
2
Order By: Relevance
“…In the RA model, co-administration of IL-12 (a potent Th1 inducing cytokine) with RA vaccine resulted in almost sterile immunity which was associated with a high induction of IFN-γ in an autocrine manner (Wilson and Coulson 2009; Wilson et al 1999; Wilson et al 2016). Studies by our group and other colleagues have shown that the production of IFN-γ is associated with protection against schistosome infection in animal models (Ahmad et al 2009c; Le et al 2014; Pearson et al 2012; Varaldo et al 2004; Zhang et al 2011). The protective role of TNF-α against schistosomiasis has also been demonstrated by the RA vaccine model (Street et al 1999).…”
Section: Discussionmentioning
confidence: 82%
“…In the RA model, co-administration of IL-12 (a potent Th1 inducing cytokine) with RA vaccine resulted in almost sterile immunity which was associated with a high induction of IFN-γ in an autocrine manner (Wilson and Coulson 2009; Wilson et al 1999; Wilson et al 2016). Studies by our group and other colleagues have shown that the production of IFN-γ is associated with protection against schistosome infection in animal models (Ahmad et al 2009c; Le et al 2014; Pearson et al 2012; Varaldo et al 2004; Zhang et al 2011). The protective role of TNF-α against schistosomiasis has also been demonstrated by the RA vaccine model (Street et al 1999).…”
Section: Discussionmentioning
confidence: 82%
“…44 Further studies should therefore incorporate Sm-A 263 K into a P25 bearing multiepitope LCP-based vaccine with protective epitopes from other lead vaccine antigens including Sm-TSP-2, Smp80-calpain 45 and Sh-GST28.…”
Section: Discussionmentioning
confidence: 99%
“…Development of an effective vaccine has the potential for making a considerable impact. A chimeric vaccine fusion of the antigens for both hookworm and Schistosoma parasites (Sm-TSP-2 and Na-APR-1) was recently used successfully in an experimental murine challenge study [43]. This vaccine is particularly suitable for use in areas with endemicity for both diseases.…”
Section: Preventionmentioning
confidence: 99%